Pengaruh Infrastruktur Ekonomi terhadap Pertumbuhan Ekonomi di Kabupaten Probolinggo (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Economic growth is a crucial pillar of regional development and serves as an indicator of how well development is going as well as a tool for future planning. Development will not proceed easily if the infrastructure is poor, and a nation or region's economic activity will not be sufficient if the infrastructure is insufficient. Throughout the years 2018 to 2024, Probolinggo Regency's economic growth rate development had erratic variations. Therefore, the purpose of this study is to ascertain how Probolinggo Regency's road network, access to clean water, and availability of power affect economic growth. This study's methodology was quantitative and deductive in nature. The information used is secondary data, specifically time series data from the Central Bureau of Statistics. Using multiple linear regression analysis and the OLS (Ordinary Least Square) data analysis method, SPSS 24 was utilized to conduct the study's data analysis. Where the value is significant > 0.05, the study's findings show that infrastructure for roads, water, and power has no bearing on economic growth.